Cuba Represent! : Cuban Arts, State Power, and the Making of New Revolutionary Cultures - Fernandes, Sujatha (Book collections on Project MUSE., 2006)
An ethnographic consideration of why the Cuban government has allowed criticism of its policies to be expressed in Cuban film, visual art, and music over the past fifteen years.